Bone morphogenetic protein‐2 and bone therapy: successes and pitfalls. (4th January 2016) - Poon, Bonnie; Kha, Tram; Tran, Sally; Dass, Crispin R.
Abstract: Objectives: Bone morphogenetic proteins (BMPs), more specifically BMP‐2, are being increasingly used in orthopaedic surgery due to advanced research into osteoinductive factors that may enhance and improve bone therapy. There are many areas in therapy that BMP‐2 is being applied to, including dental treatment, open tibial fractures, cancer and spinal surgery. Within these areas of treatment, there are many reports of successes and pitfalls. This review explores the use of BMP‐2 and its successes, pitfalls and future prospects in bone therapy. Methods: The PubMed database was consulted to compile this review. Key findings: With successes in therapy, there were descriptions of a more rapid healing time with no signs of rejection or infection attributed to BMP‐2 treatment. Pitfalls included BMP‐2 'off‐label' use, which lead to various adverse effects. Conclusions: Our search highlighted that optimising treatment with BMP‐2 is a direction that many researchers are exploring, with areas of current research interest including concentration and dose of BMP‐2, carrier type and delivery.